A realist evaluation of a regional Dementia Health Literacy Project. (2nd January 2019) - Grace, Sandra; Horstmanshof, Louise
Abstract: Background: A Dementia Health Literacy Project was undertaken in the north coast region of NSW, Australia, after it was identified as having a high prevalence of dementia. A Dementia Support Kit was produced with service user engagement to provide useful information to people with dementia and their families. Objective: To evaluate the Dementia Health Literacy Project using a realist evaluation framework. Setting and participants: The setting was the region of the north coast of New South Wales. Eight people diagnosed with dementia and their carers, 13 members of social groups of older people in the local area, and 22 local GPs and other health‐care and service providers participated in this study. Results: Two context‐mechanism‐outcome configurations were identified: (a) co‐design workshops where the stakeholders' opinions were equally valued (context) led service users to feel listened to and prompted them to provide feedback (mechanism) to develop a practical resource that they would use (outcome); and (b) use of health professionals to distribute the resources (context) that they consider useful and valuable (mechanism) resulted in the target audience receiving the resources (outcome). Discussion and conclusions: The Dementia Health Literacy Project produced a Dementia Support Kit that is likely to provide locally relevant and useful information for people with dementia and their carers. The results highlight the value of the co‐design approach in producing and disseminating dementia health literacy resources. Further evaluation is required to confirm the impact of the Kit over time on service users' behaviour and consequently on their health outcomes.